2019
DOI: 10.1155/2019/9306803
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of Serum MicroRNAs as Early Diagnostic Biomarkers for Prostate Cancer in Chinese Population

Abstract: Prostate cancer (PCa) incidence has been rising in Chinese population. Current PSA-based biopsy has limited positive rate. Our research focused on development of serum markers for the diagnosis of PCa in patients with elevated PSA. miRNAs are found to be aberrantly expressed in many types of cancer. They are readily detectable in plasma and serum. Currently, miRNAs are being evaluated as potential prognostic and diagnostic tools for many types of cancer. We first profiled global serum miRNAs in a pilot set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
2
15
0
1
Order By: Relevance
“…This observation was also reported by other studies [10,17]. The threshold or best cut-off value was higher than what other authors reported [11,18]. This could be explained by the observation that men of Black African ancestry have been shown to have higher levels of PSA than Asian or Caucasian due to differences in androgenic and genetic in uences [21] Using a cut of the value of 5.0 ng/ml, TPSA showed a false positive rate as high as 88% and speci city as low as 12.0%, although the sensitivity was 100%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This observation was also reported by other studies [10,17]. The threshold or best cut-off value was higher than what other authors reported [11,18]. This could be explained by the observation that men of Black African ancestry have been shown to have higher levels of PSA than Asian or Caucasian due to differences in androgenic and genetic in uences [21] Using a cut of the value of 5.0 ng/ml, TPSA showed a false positive rate as high as 88% and speci city as low as 12.0%, although the sensitivity was 100%.…”
Section: Discussionsupporting
confidence: 87%
“…Further evidence of the association between PSA and PCa was shown by a signi cant increase in ageadjusted odds ratios with increasing TPSA levels, similar to the ndings by Nakamura, Scorilas [17] and Lyu, Zhao [18].…”
Section: Discussionsupporting
confidence: 80%
“…A panel of 5 parameters including PSA, prostate volume, and serum levels of miR-4286, miR-27a-3p, and miR29b-3p was considered by Lyu et al [ 158 ]. The panel was compared in PCa ( n = 78) and BPH ( n = 77) patients and revealed excellent diagnostic performance in separating the two populations (AUC 0.892, 95% CI: 0.832–0.937, sensitivity 78.95%, and specificity 92.21%) as well as in recognizing the early-stage disease.…”
Section: The Diagnostic and Prognostic Power Of Mirnas In Prostatementioning
confidence: 99%
“…24,25 It can be detected by miR-424 combined with PSA value and prostate volume to assist in the diagnosis of prostate cancer in patients with elevated PSA. 26 In addition to studies on endocrine organs, the association between miRNAs and digestive system tumors has also been explored. The overall survival rate of pancreatic adenocarcinoma (PAAD) is associated with miRNAs including miR-424, which may have the potential to become a prognostic biomarker for PAAD.…”
Section: Dual Regulatory Function Of Mirna-424mentioning
confidence: 99%